Beyond Formal Courts: The Role of Customary Institutions in Resolving Divorce Disputes in East Aceh, Indonesia - Nabila Miswar; Ida Friatna; Riza Afrian Mustaqim; Maryna Chernysh; Munkh-Erdene Batdulam (Yayasan Cendekia Gagayunan Indonesia, 2026)
This study examines the authority, effectiveness, and practices of divorce dispute resolution conducted by customary institutions in Lhok Dalam Village, Peureulak District, East Aceh, Indonesia. The research addresses the growing interaction between customary mechanisms and formal religious courts in resolving family disputes within Acehnese society. Using a qualitative socio-legal approach, data were collected through in-depth interviews with customary leaders and community members, field observations, and document analysis. The data were analyzed using descriptive-analytical techniques to identify patterns of authority, mediation practices, and institutional limitations within the customary dispute resolution process. The findings reveal that customary institutions possess strong moral and social legitimacy in mediating marital conflicts before cases are submitted to the Mahkamah Syar’iyah. Divorce disputes are generally addressed through deliberative dialogue, religious advice, and reconciliation efforts (islah) aimed at restoring family harmony. This process is perceived as effective in reducing social tensions, preventing premature divorce, and preserving community dignity and social cohesion. However, the study also finds that the effectiveness of customary mediation remains institutionally limited because the outcomes lack formal legal recognition within the state legal system. Consequently, decisions reached through customary mediation cannot always guarantee legal certainty for the parties involved. This study recommends strengthening the role of customary institutions by establishing formal documentation of mediation outcomes, enhancing the capacity of customary leaders through legal and mediation training, and developing institutional collaboration with the Mahkamah Syar’iyah to ensure both social legitimacy and legal certainty in divorce dispute resolution.